Solusi Pembelajaran Anak Usia Dini di Era Pandemi dengan Metode Pembelajaran berbasis Hiburan Edukasi (Current Research in Education: Conference Series Journal, 2022)
Covid-19 is declared a pandemic that has spread to all parts of the world. The spread is so fast that it takes the best effective way to prevent transmission. One way is to keep a distance in order to break the chain of transmission. The statement explains that not to cluster in one room, as in learning, namely by learning in the classroom. This has led to changes in learning nationally, emerging with the phrase "Learning from home online (online)". During the current pandemic, educators are very worried about the character and personality development of early childhood. This is because students with a very young age vulnerable will have difficulty if they do not receive education directly. Early Childhood Education (PAUD) itself is a level of education taken by children before entering elementary school (SD). Early childhood education is a training intended for children aged 0-6 years, where this age becomes the golden age in shaping children's personality and character. In learning on early childhood education during a pandemic like this, it relies heavily on parents as a facility to direct children in learning that should be carried out like regular educators, the reason is that if parents cannot teach and educate their children it will be difficult for the child to develop a form of thought and the child's personality as a result of learning from home. In this case the writing of the following article aims to provide solutions to the handling of the learning process in early childhood with various methods which are considered to provide broader insights.